Principles of pharmacological correction of pulmonary arterial hypertension - Mikhail Korokin; Nina I. Zhernakova; Liliya Korokina; Olga Pokopejko (Belgorod National Research University, 2018)
Definition and classification: Pulmonary hypertension (PH) is a group of life-threatening progressive diseases of various genesis, characterized by a progressive increase in arterial pressure (AP) in the pulmonary artery (PA), the remodeling of pulmonary vessels, which leads to an increase in pulmonary vascular resistance and pulmonary arterial pressure and more often leads to right ventricular heart failure and premature death. Pulmonary hypertension is clinically divided into five groups: patients in the first group have idiopathic pulmonary arterial hypertension (IPAH), whereas in patients of other groups secondary PH associated with cardiopulmonary or other systemic diseases is observed. The development of secondary LH is caused by congenital heart defects, collagenoses, presence of thrombus in the pulmonary artery, prolonged high pressure in the left atrium, hypoxemia, chronic obstructive pulmonary diseases (COPDs). In case of secondary PH, thrombosis and other changes in the pulmonary veins occur. Ways of pharmacological correction of pulmonary hypertension: Over the last decade pharmacotherapy of PH has been developing rapidly, and the introduction of modern methods of treatment, especially for primary PAH, has led to positive results. However, despite the progress in treatment, the functional limitations and survival of patients remain unsatisfactory. Currently, there are two levels of treatment for pulmonary hypertension: primary and specific pathogenetic therapies. Primary therapy is aimed at the main cause of PH. It also includes supportive therapy. Pathogenetic therapy includes prostanoids, endothelin receptor antagonists, and phosphodiesterase-5 inhibitors. Tactics of therapy can be established on the basis of either clinical classification, or functional class. Prostanoids are a promising group of drugs for the treatment of pulmonary arterial hypertension (PAH), since they possess not only vasodilating, but also antiplatelet and antiproliferative actions. Therefore, it seems logical to use prostacyclin and its analogs to treat patients with various forms of PAH.